Book Review: Experimentelle Archäologie in Europa, Jahrbuch 2020 - Stefanie Ulrich (EXARC Journal)
The periodical (Jahrbuch) was published by Gunter Schöbel and the European Asssociation for the advancement of archaeology by experiment e. V. (Europäische Verinigung zur Förderung der Experimentellen Archäologie) in collaboration with the Pfahlbaummuseum Unterhuldingen. The 19th issue of the periodical includes 19 essays over 231 pages which present the contributions of the EXAR conference held in 2019. The annual report (Jahresbericht, p.225) and the instructions for authors (Autorenrichtlinien, p.229) of Experimentelle Archäologie in Europa can be found at the end.